STRATEGI HARGA : DISKON DAN ANGKA DIGIT - Tri Aprilisa Shabariyatun; Suliyanto Suliyanto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2012)
This research use experimental method, the experimental designs examine two variables which will compare in the result. In this research there are two kind of two pricing strategy, there are price discount and price ending. Each strategy will compare two variable, there are buying attitude and intention. The numbers of sample are 80 participants from student senior high school. In this research there are two groups of treatment, group A and group B. To measure the result used One-way ANOVA. And then, to measure the relation between variable regression linear used as the examination supporting tool. According to the result, finds that: costumer attitude to the price ending more highly than to the price discount; costumer intention to the price ending more highly than to the price discount; there is costumer intention positive attitude in price ending type.